2020
DOI: 10.1177/0004867420951256
|View full text |Cite
|
Sign up to set email alerts
|

Suicide ideation versus suicide attempt: Examining overlapping and differential determinants in a large cohort of patients with depression and/or anxiety

Abstract: Objective: Individuals with a depressive and/or anxiety disorder are known to have an elevated risk of suicide. However, these diagnoses alone are insufficient at differentiating patients with suicide ideation that attempt suicide from those that do not. Few studies examined such differences in an ideation-to-action framework. Using this framework, extensive multivariate testing was performed to examine differences between suicidal patients with and without a suicide attempt. Method: Data were from 1576 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 43 publications
3
23
1
Order By: Relevance
“…Previous studies have reported that there are factors distinguishing those with suicide attempts from those who have experienced suicidal ideation but never attempted suicide. A markedly high presence of depressive disorder or hopelessness was seen in suicide ideators, and suicide attempters could be distinguished by a higher prevalence of comorbid substance use disorder, a younger age of onset, and a lack of social support [ 31 , 32 ]. The capability to attempt suicide caused progression from ideation to attempts [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that there are factors distinguishing those with suicide attempts from those who have experienced suicidal ideation but never attempted suicide. A markedly high presence of depressive disorder or hopelessness was seen in suicide ideators, and suicide attempters could be distinguished by a higher prevalence of comorbid substance use disorder, a younger age of onset, and a lack of social support [ 31 , 32 ]. The capability to attempt suicide caused progression from ideation to attempts [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-anxiety individuals may have an external locus of control (i.e., feeling one's life is controlled by external factors); perceived lack of control may facilitate feelings of hopelessness that, in theory, exacerbate suicidal ideation (Joiner, 2005). Indeed, having an external locus of control has been associated with suicide attempts (Wiebenga et al, 2021). It is also possible that 'high anxiety' is a proxy for overarousal and/or sensitivity to the experience of anxiety, both of which have been suggested as risk factors for suicide (Ribeiro et al, 2015;Stanley et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health issues are often co-morbid with other disorders. Suicide ideation is predicted by sleep problems, insomnia, depression, and anxiety ( Khader et al, 2020 ; Wiebenga et al, 2021 ). Worryingly, the association with sleep problems and suicide ideation is stronger amongst college athletes than non-athletes ( Wiebenga et al, 2021 ).…”
Section: Research Strategymentioning
confidence: 99%
“…Suicide ideation is predicted by sleep problems, insomnia, depression, and anxiety ( Khader et al, 2020 ; Wiebenga et al, 2021 ). Worryingly, the association with sleep problems and suicide ideation is stronger amongst college athletes than non-athletes ( Wiebenga et al, 2021 ). Thus, it is unsurprising that 15.6% of collegiate athletes report suicide ideation, with some unfortunately, attempting and committing suicide ( Rao and Hong, 2016 ; Timpka et al, 2021 ; Wiebenga et al, 2021 ).…”
Section: Research Strategymentioning
confidence: 99%